Livestock product processing technology - Priyadarshini, Aparajita; Ismail, Muhammad Heikal; Singh, Ashutosh; Routray, Winny (Elsevier, 2024)
Livestock production has increased spectacularly attributed to development in animal health, nutrition, genetics, and breeding, wherein the processes involved have been crucial for the changing environment. The global livestock segment is one of the major contributors to environmental pollution challenges, at every level, from local to global. Currently, the reduction of environmental losses and the involvement of efficient technologies for livestock production are some of the suggested targeted solutions for these challenges. Moreover, the genetic improvement of livestock continues to play a key role in the advancement of the livestock product industry, which will increase the effectiveness and sustainability of livestock production for all respective species. The current chapter deals with the broad contribution of traditional to modern breeding technologies to livestock production, although focusing on the advancement of production, schemes and biotechnology of different livestock, and advances in processing techniques. This chapter includes updates about developments and milestones, which have contributed to the improvement of livestock with emerging opportunities for future growth.